# Prove the identity: (tan^2x/1+tan^2x) + (cot^2x/1+cot^2x)= (1-2sin^2xcos^2x)/sinxcosx

*print*Print*list*Cite

Expert Answers

justaguide | Certified Educator

The identity that has to be proved is :(tan x)^2 / ( 1 + (tan x)^2) + (cot x)^2 /(1 + (cot x)^2) = (1 - 2*(sin x)^2 (cos x)^2)/sin x cos x

Start with the left hand side:

(tan x)^2 / ( 1 + (tan x)^2) + (cot x)^2 /(1 + (cot x)^2)

=> (tan x)^2 / ( 1 + (tan x)^2) + (1/tan x)^2 /(1 + (1/tan x)^2)

=> (tan x)^2 / ( 1 + (tan x)^2) + [1/(tan x)^2]/[(1 + tan x)^2)/(tan x)^2]

=> (tan x)^2 / ( 1 + (tan x)^2) + 1/(1 + tan x)^2)

=> ((tan x)^2 + 1) / ( 1 + (tan x)^2)

=> 1

The right hand side:

(1 - 2*(sin x)^2 (cos x)^2)/sin x cos x

=> (1/ sin x cos x) - 2*sin x cos x

=> 2/sin 2x - sin 2x

this cannot be equated to 1.

**We do not have an identity here.**